Yes Minister - Series One Episode 1-7 - Lotterby, Sydney; Eddington, Paul; Hawthorne, Nigel; Fowlds, Derek (BBC Worldwide, 2001)
A benchmark for quietly civilised yet scalpel-sharp political satire, "Yes, Minister" is deservedly regarded as one of British sitcom's finest achievements. Maintaining an enviable quality threshold over 22 episodes (1980-84) and 16 of "Yes, Prime Minister" (1986-88), its many fans included the then Prime Minister Margaret Thatcher. Like all classic sitcoms, it's based on a very simple observation: that for all its claims towards democracy, the British political system is largely run by unelected civil servants who run Machiavellian rings around their supposedly superior masters. As this is just as true today, Yes, Minister has hardly dated at all ... [www.screenonline.org.uk]